Influence of sliding velocity on wear behaviour of different microstructures of Ni-Cr-Mo-V steel - Rai D.; Pathak J.P. (My University, 2025)
The effect of sliding velocity on wear property of six microstructural states of Ni-Cr-Mo-V crane wheel steel under 4 kg load has been studied and discussed in detail. The steel with 0.35 wt.% C, 0.68 wt.% Mn, 0.30 wt.% Si, 0.014 wt.% S and P, 0.68 wt.% Cr, 3.10 wt.% Ni, 0.40 wt.% Mo, 0.11 wt.% V, balance iron was hardened and tempered at 225, 350, 450 and 550°C to develop martensite and various hardened and tempered martensite microstructures. With the help of controlled furnace cooling, a bainitic structure was also developed. It was found that an increase in the tempering temperature increased percentage elongation and reduction in area but decreases the tensile strength. It was observed that increasing the velocity increased the wear rate but beyond a certain sliding rate, wear decreased with an increase in sliding velocity. Wear mechanism changed from mild/oxidative to severe/metallic and then to oxidative with increasing the sliding velocity. Hardened martensite showed highest wear resistance compared with various tempered martensite. Martensite tempered at a lower temperature possessed a higher wear resistance as compared to martensite tempered at a higher temperature. The bainitic microstructure showed the highest wear rate in all cases irrespective of velocity.